Effectiveness of the Integrated Administrative Information System (PATEN) in Public Service (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2024)
Problems related to population administration and civil registration, such as identity falsification and duplicate data due to lack of accurate details of population data documents, the process of obtaining a Population Identity Card and issuing a civil registration certificate still takes a long time because the data input process is still done manually. In this regard, the Garut Regency government, in this case the Tarogong Kaler District, is trying to collect valid population data so that it can develop mapping to overcome this problem. Currently there is an information system that makes it easier to provide services for creating and issuing resident document certificates, namely by implementing a website-based integrated administration service system or PATENT. This research aims to analyze Effectiveness of the Integrated Administrative Information System (PATEN) in Public Service. This research uses a qualitative descriptive type of research with four informants.   Data collection techniques start from direct observation, interviews, and documentation.  The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions and verification. The results of the research show that the community can enjoy the quality of services provided in Tarogong Kaler District. This can be seen from several things. The reliability dimension can be seen from the district operators who are reliable in providing services to the community. The responsiveness dimension related to the ability to respond is said to be good if the PATENT system has immediate disruption. can be overcome by not reducing services to the community. The obstacles are that the availability of human resources is still insufficient, as well as the need for socialization to the community about understanding the system.
Keywords: Population; services; PATEN; website